Diversity of Pteridophytes in Mount Timolan Protected Landscape, Zamboanga del Sur, Philippines - Maricris G Cudal; Liberty Grace L Calimbo; Diosdado Sumibay Jr; Jaidel Salise; Jessa Gomez; Meraflor Pagaling; Jasper Locson; Joel Cahayagan; Jernol Seno; Jahuel Nathan Daculio (Journal of Tropical Life Science, 2021)
This study serves as the first generation research on the rich yet not poorly known ferns and lycophyte species of the Mount Timolan Protected Landscape (MTPL). A total of 151 species from 62 genera and 24 families were recorded from December 2019-May 2019. Overall, the species of MTPL respectively holds 14%, 40% and 71% of the recorded total species, genera and families of ferns and lycophytes in the Philippines. The most represented families in terms of the number of genera is Polypodiaceae (10 spp.), whereas, the most represented genera in terms of the number of species were Selaginella (11 spp.). The results of the study showed that Mount Timolan Protected Landscape harbours number of some endemic species (17 spp.), critically endangered species (1 spp.), endangered species (3 spp.), vulnerable species (5 spp.), threatened, non-native species and economically important species (25 spp.). Based on conservationÂ and ecological status of assessed ferns and lycophyte species, it is likely to strongly suggest to set species-specific conservation management strategy to protect the threatened species. However, additional studies and thorough field explorations should also be done to conduct a re-inventory on the pteridophyte species in order to arrive a more scientific results to establish a real profile of the ferns and lycophyte species of Mount Timolan Protected Landscape.